QRS-T morphology measured from exercise electrocardiogram as a predictor of cardiac mortality - Kentta, T.; Karsikas, M.; Junttila, M. J.; Perkiomaki, J. S.; Seppanen, T.; Kiviniemi, A.; Nieminen, T.; Lehtimaki, T.; Nikus, K.; Lehtinen, R.; Viik, J.; Kahonen, M.; et al. (Europace (London, England), 2011)
Total cosine R-to-T (TCRT) measured from the standard 12-lead electrocardiogram (ECG) reflects the spatial relationship between depolarization and repolarization wavefronts and a low TCRT value is a marker of poor prognosis. We tested the hypothesis that measurement of TCRT or QRS/T angle from exercise ECG would provide even more powerful prognostic information. The prognostic significances of TCRT and QRS/T angle were assessed from exercise ECG recordings in 1297 patients [age 56 ± 13 years (mean ± SD), 67% males] undergoing a clinically indicated bicycle stress-test and the subsequent follow-up. During an average follow-up of 45 ± 12 months, 74 patients died (5.7%); 34 (2.6%) were cardiac deaths, and 24 (1.9%) were sudden cardiac deaths. Total cosine R-to-T and QRS/T angle exhibited a correlation with the RR intervals in the total cohort, but the individual responses were variable, e.g. median correlation of TCRT-RR was 0.89 with an inter-quartile range from 0.55 to 0.98. A reduced correlation of TCRT-RR during the recovery phase of exercise ECG predicted cardiac death [adjusted heart rate (HR) 3.5, 95% confidence interval (CI): 1.8-6.8, P= 0.001] similarly as the baseline TCRT measured from ECG at rest (adjusted HR 3.4, 95% CI: 1.4-8.1, P= 0.01). The poor correlation between the TCRT-RR both during the exercise and recovery was specifically related to a risk of sudden cardiac death (adjusted HR 6.2, 95% CI: 2.1-17.8, P< 0.001). Loss of rate-adaptation of the spatial relationship between depolarization and repolarization wavefronts is a strong predictor of cardiac death, especially of sudden cardiac death.